Efek Antikanker Nanopartikel Alginat Ekstrak Etanol Daun Sirsak (Annona muricata Linn) pada Kultur Sel Kanker Hepar (HepG2) - Adila Putri Ramandhita; Listya Hanum (Jurnal Riset Kedokteran, 2022)
Abstract. Liver cancer is the second leading cause of cancer death globally in 2020. One of the treatment options for liver cancer is chemotherapy. Chemotherapy for liver cancer still has many side effects and high incidence of resistance. One of the efforts to overcome this problem is the development of phytopharmaceuticals. Soursop leaf extract (Annona muricata L.) has been studied and showed various anticancer effects such as cytotoxicity, induction of apoptosis, necrosis, and inhibition of proliferation. Herbal extracts are being developed in nanoparticle preparations because they can increase bioavailability. The purpose of this study was to examine the anticancer effect of alginate nanoparticles (NP) ethanol extract of soursop leaf (Annona muricata L.) on HepG2 liver cancer cell cultures. This study is an experimental study in vitro on HepG2 liver cancer cell cultures. Cytotoxicity test was carried out using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. The IC50 value was obtained by probit regression analysis using software SPSS. The results showed that the IC50 NP alginate of soursop leaf ethanol extract was 14.5 g/mL. In conclusion, NP alginate ethanolic extract of soursop leaves has a high anticancer effect on HepG2 liver cancer cell cultures. The anticancer effect can be caused by the content of annonaceous acetogenin (AGE) and flavonoids. Abstrak. Kanker hepar merupakan penyebab kematian kanker terbanyak kedua secara global pada tahun 2020. Salah satu pilihan terapi kanker hepar adalah kemoterapi. Kemoterapi untuk kanker hepar masih memiliki banyak efek samping dan kejadian resistensi yang tinggi. Salah satu upaya mengatasi masalah tersebut adalah dengan pengembangan fitofarmaka. Ekstrak daun sirsak (Annona muricata L.) telah diteliti dan menunjukkan berbagai efek antikanker seperti sitotoksisitas, induksi apoptosis, nekrosis, dan penghambatan proliferasi. Ekstrak herbal sedang dikembangkan dalam sediaan nanopartikel karena dapat meningkatkan bioavailabilitas. Tujuan penelitian ini adalah menguji efek antikanker nanopartikel (NP) alginat ekstrak etanol daun sirsak (Annona muricata L.) terhadap kultur sel kanker hepar HepG2. Penelitian ini merupakan penelitian eksperimental in vitro terhadap kultur sel kanker hepar HepG2. Uji sitotoksisitas dilakukan menggunakan metode 3-(4,5-dimethylthiazol-2-yl)-2,5-difenil-2H-tetrazolium bromida (MTT) assay. Nilai IC50 didapatkan dengan analisis regresi probit menggunakan software SPSS. Hasil penelitian menunjukkan IC50 NP alginat ekstrak etanol daun sirsak sebesar 14,5 μg/mL. Simpulan, NP alginat ekstrak etanol daun sirsak memiliki efek antikanker tinggi pada kultur sel kanker hepar HepG2. Efek antikanker tersebut dapat disebabkan oleh kandungan annonaceous acetogenin (AGE) dan flavonoid.